The Influence of Ethanol Feeding on the Activities of Factors II, VII, VIII, IX and X in Rats - Mørland, Jørg; Holm, Turid; Prydz, Hans (Thrombosis and Haemostasis, 1976)
The effect of chronic administration of ethanol to rats in a controlled regimen upon the activities of the coagulation factors II, VII, VIII, IX and X has been studied.No significant differences were found for factor II, IX and X between the ethanol-treated rats and the control group given an isocaloric diet with carbohydrate replacing ethanol. Factor VII activity was somewhat higher and factor VIII activity decreased significantly in the experimental group when ethanol treatment was combined with an approximately two-fold increase in dietary polyunsaturated fatty acid.